Do Palestinian Workers’ Remittances from Israel and its Volatility Matter for the Palestinian Economy? - Hassouneh, Islam (Journal of Reviews on Global Economics, 2020)
This paper studies the impact of Palestinian workers’ remittances from Israel and its volatility on Palestinian economic growth using quarterly data over the period 2000-2016. A joint estimation of a vector error correction and multivariate generalized autoregressive conditional heteroskedasticity models are applied for such purpose. Cointegration tests provide evidence of a long-run positive equilibrium relationship between remittances and output growth. Results also indicate that remittances have influence on both first and second moments of Palestinian GDP. Further, findings suggest that while Palestine GDP has no influence on the first moment of Palestinian workers’ remittances from Israel, it can cause an increase in its volatility.